Pemidanaan Kepala Daerah yang Terduga Korupsi Akibat Operasi Tangkap Tangan oleh Komisi Pemberantasan Korupsi - Tutik, Titik Triwulan (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
The Hand Arrest Operation (OTT) against Regional Heads suspected of committing criminal acts of corruption is a juridical authority given to the KPK in the context of efforts to eradicate corruption. OTT by the KPK can only be carried out with the following conditions: First, as long as there is “preliminary evidence”, “sufficient preliminary evidence”, and “sufficient evidence”. Second, continue to uphold human rights to the suspect. The prosecution of regional heads who are suspected of committing criminal acts of corruption through the KPK's Hand Arrest Operation (OTT) is carried out in three forms. First, the death penalty as regulated in Article 2 paragraph (2) of the 1999 PTPK Law in conjunction with the Corruption Act 2001. Second, imprisonment and fines, which are regulated in Article 5, Article 6, Article 7, Article 8, Article 9, Article 10, Article 11 and Article 12 of the Corruption Act 1999 in conjunction with the Corruption Act 2001. Apart from that, it is also provided for in Article 55 Paragraph 1 to 1 of the Criminal Code. Third, the additional penalty for substitute money is regulated in the Supreme Court Regulation Number 5 of 2014 concerning the additional penalty for Corruption Crimes. Given that corruption is an extraordinary crime and its prevention requires special steps. Therefore, it is necessary to synchronize the rule of law between the Criminal Procedure Code and the Corruption Act in supporting the existing legal system to be more effective.